Advantages and disadvantages of e-learning innovations during COVID-19 pandemic in higher education in Poland - Kinga Stecuła; Radosław Wolniak (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The paper presents the results of the research on the advantages and disadvantages of innovative e-learning during the COVID-19 pandemic in higher education. In the first stage, an internet questionnaire was used for the study. The research was carried out in Poland on a sample of 621 students. The results allowed the researchers to determine variables that are important for the proper implementation of innovative e-learning, and the emergent perspectives for this form of education after the end of the COVID-19 pandemic. Among the most significant disadvantages, there was a lack of direct contact with colleagues, difficulties with teaching practical subjects, lack of direct contact with the teacher, and too much time spent in front of a computer/telephone or other mobile device. The most important correlations included the following: students satisfied with e-learning assess the advantages highly and the disadvantages lower; all the advantages of innovative e-learning are positively correlated with the student's assessment of the ease of acquiring content in e-learning, and negatively correlated with the student's assessment of the ease of acquiring content in traditional education; the easier the student assimilates innovative e-learning content, the higher the student's evaluation of the advantages of e-learning; students who perceive e-learning content as difficult to absorb have low motivation to learn remotely; the better the student knows information technology, the more highly the student evaluates the advantages of innovative e-learning; the better resources to participate in e-learning activities the student has, the higher the student's evaluation of the advantages of e-learning; the more often innovative e-learning solutions are used in a given university, the better the student assesses the advantages of e-learning.
Keywords: 650; COVID-19 pandemic; open innovation; advantages of e-learning; disadvantages of e-learning; e-learning; innovative education